Comportamento de leitões na fase de creche com enriquecimento ambiental - Boaretto, Joselaine Bortolanza Padilha (2018)
The aim of this research was to evaluate the effect of environmental enrichment on piglet behavior during the nursery phase, during different seasons of the year. The experiment was carried out on a commercial farm in the city of Dois Vizinhos, Paraná, in two stages, summer (from February 11th to March 11th, 2017) and winter (June 10th to July 8th, 2017). A total of 900 piglets in the post-weaning phase were used (21 days of age), 450 in the summer and 450 in the winter, weighing approximately 6 kg, hybrids, both females and uncastrated males. The treatments were divided as follows: NEE treatment: no environmental enrichment in the stalls (control); IEE treatment: intermittent environmental enrichment with a rubber ball, during the entire experimental period, and IEE treatment: intermittent environmental enrichment with a rubber ball, during the entire experimental period. During the latter treatment, the balls were removed daily for washing. Ten animals per stall were randomly selected for behavioral evaluations, performed once a week, from 8 AM to 6 PM, using images captured with a video camera. The variables temperature and relative air humidity were recorded daily by means of thermohygrometers. Regarding statistical analyses, analyses of variance were performed using the GLM procedure and the means were compared by Tukey’s test at a significance level of 5%. During summer and winter, ideal temperature values for the nursery phase were not met. Regarding the behavioral evaluations during both periods, the piglets interacted more frequently with the rubber balls that were removed from the stalls, washed and returned daily (IEE treatment), and displayed the highest number of ball accesses during this treatment compared to the CEE. In the summer, playful, lying and belly nosing behaviors were significantly influenced by the treatments. Piglets that underwent the IEE treatment presented a higher frequency of playful behavior. The animals maintained without environmental enrichment spent more time lying down than those that underwent the continuous and intermittent environmental enrichment treatments. The animals submitted to the treatments with environmental enrichment performed less belly nosing behavior compared to those without environmental enrichment. During winter, the treatments significantly influenced eating and playful behaviors. Regarding eating behavior, the animals that underwent the IEE treatment ate less food compared to the others. Regarding playful behavior, a higher frequency of playfulness was observed for the piglets that underwent the CEE treatment. These results indicate that the environmental enrichment during summer stimulated the active behavior of the piglets and was efficient in reducing belly nosing behavior. During winter, natural behaviors were not stimulated and there was no decrease of stereotypies.